1996
DOI: 10.1159/000189477
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-Associated Renal Tuberculosis

Abstract: In order to study the prevalence and the clinical features of renal tuberculosis associated with AIDS, we studied the renal tissue of the necropsies made in 46 AIDS patients under light microscopy. We found renal tuberculous granuloma in 11 (23%) patients (in 3 without previous diagnosis of renal or extrarenal tuberculosis) and only 4 of them presented moderate hematuria or pyuria sterile. As subclinical renal tuberculosis was frequent in this group of AIDS patients, the urine culture for Mycobacterium tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…In autopsy studies of patients with AIDS, renal TB was identi®ed in 6±23% [22,23]. Although most of these patients had signs and symptoms of pulmonary TB, 20% had subclinical disease [22]. M. tuberculosis is the most frequent cause of renal TB, and less frequently M. avium and M. intracellulare [24].…”
Section: Opportunistic Infectionsmentioning
confidence: 99%
“…In autopsy studies of patients with AIDS, renal TB was identi®ed in 6±23% [22,23]. Although most of these patients had signs and symptoms of pulmonary TB, 20% had subclinical disease [22]. M. tuberculosis is the most frequent cause of renal TB, and less frequently M. avium and M. intracellulare [24].…”
Section: Opportunistic Infectionsmentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) infection increases the risk of tuberculosis either by reactivation of latent foci, or by rapid progression of a newly acquired infection or reinfection [3]. Between 20% and 50% of the HIV-infected population worldwide have active tuberculosis [4,5]. Thirty percent of the world population (1.7 billion people) are estimated to harbor Mycobacterium tuberculosis, and although more than 90% of the new cases of tuberculosis occur in developing countries, the higher incidence of AIDS-related tuberculosis makes this infection a chief concern even in developed countries [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, from 1,282 patients diagnosed with tuberculosis between 1991 and 1997 in an inner-city hospital, 46% had HIV coinfection [6]. An autopsy study of 46 AIDS patients in Brazil revealed that 54.3% had tuberculosis, the disseminated form being the most frequent one [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal tuberculosis (TB) is uncommon in children, but needs to be considered especially in disseminated disease as specific interventions would be required 1–3 . An increase in the incidence of renal TB can be anticipated with the spread of the AIDS 4 . Imaging of renal TB in children differs from adults in that intravenous urography (IVU) is no longer considered a routine investigation for renal tract symptoms because of the radiation burden.…”
Section: Introductionmentioning
confidence: 99%